BIBLIOMETRIC ANALYSIS OF ENTREPRENEURSHIP EDUCATION IN SCOPUS-INDEXED JOURNALS - Sultono, Sultono; Barliana, M Syaom; Aryanti, Tutin; Suryadi, Dedy (UNIVERSITAS NEGERI SURABAYA, 2025)
The aim of this study is to understand the roles, trends, and development of research in entrepreneurship education. The method used is bibliometric analysis with the help of tools such as OpenRefine, VOSViewer, MS Excel, and Bibliometrix. These tools were used to analyze document distribution per year across different countries, institutions, journals, authors, topic trends, and keyword co-occurrences. The search was conducted on August 10, 2024, the literature search was conducted by entering words based on the title, abstract and keywords